Ende einer Monopolisierung - Glaube im öffentlichen Raum - Angel, Hans-Ferdinand (Theo-Web, 2016)
Belief in our country is mostly if not exclusively associated with religion or the church. This is a problem. It prevents an understanding of belief as an anthropological possibility not confined to the context of religion. It also prevents an understanding of belief as a process in time. But it is just the understanding of what goes on in a human being when he or she is (in the act of) believing that can activate those communicative potentials needed for educationally accompanying believers that are essential for a "Public Religious Pedagogy". (English)